Tensoes Residuais na Soldagem, Aspectos Basicos - Antunes, Augusto Eduardo Baptista [UNESP] (My University, 1995)
The purpose of this paper is to analyze the basic aspects of the residual stresses in welding. Concepts about macro and micro residual stresses in metals are considered in welding. In a simple welding model is shown how shrinkage macro stress results and how this can contribute to understand the distribution of residual stresses in common type of welded joint. Further, comments are made concerning the effects of additional mechanical and metallurgical phenomena, distortion in weldments and dimensional discrepancies.
Residual stresses in welding: basic aspects
Keywords: Joints (structural components); Mathematical models; Metallurgy; Residual stresses; Shrinkage; Stress analysis; Stress concentration; Welds; Dimensional discrepancies; Macro stresses; Micro stresses; Welding model; Weldments; Welding